"Ukuthwasa" in the Methodist Church of Southern Africa: A Consideration of Some Opportunities Presented by Christian Engagements with African Indigenous Religion - Forster, Dion Angus (Interreligious studies and intercultural theology, 2023)
The postcolonial era has brought a renewed appreciation of African Indigenous Religion and culture among some Southern African Christians. However, because of Southern Africa’s colonial religious heritage, some African Christians are opposed to a constructive engagement with African religiosity and practice. Others seem to operate with a double consciousness - participating in African Indigenous religious ceremonies and holding African religious beliefs during the week while claiming to be Christians on Sunday. This article engages the Methodist Church of South Africa’s consideration of ukuthwasa and the practice of being a Traditional Healer in light of some instances of "double consciousness". It argues that this engagement is a form of religious pluralism that requires intentional and critical consideration. After introducing the concept of ukuthwasa and recent discussions around being both a Christian minister and a Traditional Healer, some examples of African Christian double consciousness among some members of the Methodist Church of Southern Africa are examined. Based on this critical reflection, some possibilities that Christian engagements with African religion and culture might offer for the contextualisation and decolonisation of Southern African Christianity are presented.